Jimpitan Digital: Model Inovasi Sosial bagi Masyarakat Urban untuk Meningkatkan Solidaritas Sosial - Yusuf Adam Hilman; Muhamad Chairul Basrun Umanailo; Khoirurrosyidin Khoirurrosyidin (University of Muhammadiyah Malang, 2024)
The current development of urban society shows a change in the character of society which has become more individualistic, with a society style that is instantaneous and practical, this gives rise to problems of social solidarity and solidarity in people's lives, through innovation in this digital pinch, researchers are trying to solve this. This study used a descriptive qualitative method, involving urban communities as informants, the data taken was obtained from several community activity channels such as: social gathering groups and also recitation groups. The research results show that the digital jimpitan innovation model has succeeded in providing an alternative for making the use of collecting donations more effective and efficient